PELATIHAN GEJOG LESUNG DI SANGGAR SANGIR SEBAGAI ASET WISATA DI SITUS PURBA SANGIRAN - dwi rahmani (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
Dance training activity is the elaboration of Tri Dharma of university, The third item of Community Services is the duty and obligation of every faculty. Indonesian Arts Institute (ISI) in Surakarta, in this case the lecturer of Dance Courses felt called to devote themselves to the public.The program is expected to be conducted on an ongoing basis, as a means to increase the presence of traditional arts.Beside that, the strategic context also means the teacher can publish the Indonesian Arts Institute (ISI) in Surakarta. Finally from the activities capable of affecting more significant input from both quality and quantity. The form of activities to be carried out is more focused on the training of Gejog Lesung, which was collaborated with Gejog Lesung, dance and theater movement for Gejog Lesung Sanggar Sanggir Art Group at Ancient Site, Sangiran of Sragen Regency. The material and the result of the dance training are the various wasps of Gejog Lesung, the variety of dance movements and the dialogue in the theater. From the training result, it is a repertoire of serving that is intended for tourism packaging at Ancient Site, Sangiran of Sragen Regency. The training methods used in the Gejog Lesung training process include: Dialogical method, Group Investigation, Drill and Creative Forms method.